THE ROLE OF THE CONSTITUTIONAL COURT IN TESTING THE PRESIDENTIAL THRESHOLD LAW FOR THE 2024 PRESIDENTIAL ELECTION - Abdul Ukas Marzuki; Harmono Harmono; Solichin Solichin (Faculty of Law, Universitas Pekalongan, 2023)
Objective study This is for know The Role of the Constitutional Court in Reviewing the Presidential Threshold Law for the 2024 Presidential Election As for the method study This is a qualitative study, and research qualitative is a research method used to understand social phenomena in depth. As for the type of research used by the researcher, i.e., studies, usage studies, because the researcher can understand in a way the deep context, process, and complexity of the phenomenon researched. The research results show that the Constitutional Court has the responsibility to ensure that the presidential threshold requirements are in accordance with the constitution and the basic principles of democracy. Controversial cases in various countries and the challenges associated with presidential threshold testing demonstrate the complexity and controversy involved in these arrangementsKeywords: Constitutional Court, presidential threshold, election